2017
DOI: 10.1371/journal.pone.0189149
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of Mycobacterium tuberculosis rifampin resistance in bio-safe stained sputum smears

Abstract: Direct smear microscopy of sputum forms the mainstay of TB diagnosis in resource-limited settings. Stained sputum smear slides can serve as a ready-made resource to transport sputum for molecular drug susceptibility testing. However, bio-safety is a major concern during transport of sputum/stained slides and for laboratory workers engaged in processing Mycobacterium tuberculosis infected sputum specimens. In this study, a bio-safe USP (Universal Sample Processing) concentration-based sputum processing method (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Bacterial growth was detected on the basis of turbidity of the liquid medium, and the presence of Mtb was confirmed by MPT64 strip test (SD Bioline), ZN staining, and IS 6110 PCR ( M. tuberculosis complex specific PCR) as described . For DNA isolation, 500 μL of the liquid culture was pelleted at ∼8800 × g for 10 min in a 1.5 mL microcentrifuge tube at room temperature and processed for DNA isolation and PCR. The other part (0.5 mL) of sputum was liquefied as described . Briefly, 0.5 mL of sputum was liquefied using 2 volumes of 0.1% Dithiothreitol (DTT), followed by centrifugation at ∼8800 × g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial growth was detected on the basis of turbidity of the liquid medium, and the presence of Mtb was confirmed by MPT64 strip test (SD Bioline), ZN staining, and IS 6110 PCR ( M. tuberculosis complex specific PCR) as described . For DNA isolation, 500 μL of the liquid culture was pelleted at ∼8800 × g for 10 min in a 1.5 mL microcentrifuge tube at room temperature and processed for DNA isolation and PCR. The other part (0.5 mL) of sputum was liquefied as described . Briefly, 0.5 mL of sputum was liquefied using 2 volumes of 0.1% Dithiothreitol (DTT), followed by centrifugation at ∼8800 × g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Newer assays are available for detecting the multiple and extensively drug-resistant Mycobacterium tuberculosis. Desikan [94] and Lavania, et al [96] argued that the DNA amplification and oligonucleotide probe hybridization, Line Probe Assay (LPA), and multiple drugresistant TB (MTBDR) are viable diagnostic tools for detecting multiple drug-resistant in some TB patients. After diagnosing patients with TB, the health care providers have prescribed appropriate drug regimens to treat their TB patients.…”
Section: Diagnosis Of Tuberculosismentioning
confidence: 99%
“…AFB smears and then used in TB DST analysis using molecular and other DNA sequencing based methods [5][6][7][8][9][10][11][12]. However, most of these studies involved small sample sizes (<100 slides) and only demonstrated the performance of their assays with one or two TB specific gene targets.…”
Section: Introductionmentioning
confidence: 99%